The Charms of an American Queen Anne: Rediscovered a-lá COVID-19 - De Celis, David T. (UI Scholars Hub, 2020)
This moment, the 2020 COVID-19 pandemic, has provided an opportunity—sometimes forced via crisis, or via moments of quiet reflection—to consider the inside, interior time and space, in new ways. In America, like other countries, architectural styles have come to us from foreign lands. Numerous domestic structures were influenced by British events from the 1700s–1800s. These styles—these architectures—were transformed by local/regional/national influences and events—events like this current international pandemic—that push the proverbial pause button, and cause us to re-think design. The author, who now resides and works (along with his family) in an 1886 Queen Anne style home, contemplates the various attributes and transformations of domestic architectures and the influences that shape them over time, asking: Why Queen Anne in America? How was it Victorian? And why is it relevant today? Empirical methods include observations and precedents-analysis, design work, the study of technological advances and interior-architecture history of the Victorian era. Emphasis on domesticity acknowledges both past and present by recognizing the importance of domestic architecture from the late 1700s through the 1800s, and into the present. Thus, we better understand how/why the Queen Anne style became ubiquitous in New England, and how its attributes of innate flexibility may help us today.